DEVELOPING A HUNDRED SONGS AND GAMES BOOK TO INCREASE ELT STUDENTSâ€™ TEACHING COMPETENCY AT IAIN JEMBER - Indrayani, Ninuk; Noviyanti, Sari Dewi (Universitas Muhammadiyah Jember, 2019)
This study aims at developing â€œA Hundred Songs and Games Bookâ€ for the ELT students at IAIN Jember. Considering students teaching competency is believed to be a powerful way to make students be a professional teacher in the future. One of the teacher competencies that students need to have is the ability of using creative and innovative learning material especially for the teaching of young learners. This book is the solution for the references deficiency of English songs and games for the teaching of young learners. That is why this research is done through the development of a book which is based on the needs of sources to make an effective and enjoyable learning process. This research is developed by the use of Design and Development (D D) model. The data obtained from the experts judgment evaluation result, which is available of the expert judgment checklist. All data are both analyzed qualitatively and quantitatively using mean score and Alpha Cronbach formula. The study categorized as a succeed study since the developed material met the criteria of a suitable learning material and supported by good statistical result.